Penguatan Akhlak melalui Kitab Ta’lim Muta’alim bagi Santri Pondok Pesantren - Junedi Junedi; Arya Hasan As’ari; Mukh Nursikin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
Morals in modern times are felt to be fading. There are so many people now who are studying only oriented to the pleasures of the world regardless of how Islam will be. So with the Ta'alim Muta'alim book, it is hoped that it can help overcome the erosion of morals, wrong intentions in seeking morals, wrong in looking for teachers, and how we should choose friends in studying. The method used in the following research is a qualitative research method by describing how the method from the Ta'lim Muta'alim book in instilling morals for students. The results of the research conducted are 1) intention is the most important thing in learning, 2) choosing knowledge according to their talents or abilities, 3) looking for teachers with careful consideration and deliberation in finding teachers, 4) being patient in dealing with processes and trials during the study period, 5) friends can influence someone in studying. So it is hoped that this research will be able to provide a little knowledge about how important morals are at this time and how to study in order to get blessings from the knowledge learned